1996
DOI: 10.1254/jjp.72.261
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pharmacology and Pathophysiological Significance of Endothelin

Abstract: ABSTRACT-Since the discovery of the most potent vasoconstrictor peptide, endothelin, in 1988, explosive investigations have rapidly clarified much of the basic pharmacological, biochemical and molecular biological features of endothelin, including the presence and structure of isopeptides and their genes (endothelin-1, -2 and -3), regulation of gene expression, intracellular processing, specific endothelia converting enzyme (ECE), receptor subtypes (ETA and ETB), intracellular signal transduction following rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 266 publications
(211 reference statements)
0
108
0
1
Order By: Relevance
“…ET-1, a vasoconstrictor peptide secreted from endothelial cells, is thought to have a role in a number of vascular diseases [35]. ET-1 constricts smooth muscle by activating ET A receptors [36] and also leads to the release of endothelium-derived relaxing factor by way of the ET B receptors located on the endothelium [37].…”
Section: Discussionmentioning
confidence: 99%
“…ET-1, a vasoconstrictor peptide secreted from endothelial cells, is thought to have a role in a number of vascular diseases [35]. ET-1 constricts smooth muscle by activating ET A receptors [36] and also leads to the release of endothelium-derived relaxing factor by way of the ET B receptors located on the endothelium [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that a high vascular activity of angiotensin converting enzyme may promote a progressive deterioration of the cardiovascular system in STZ-induced diabetic rats (Piper et al, 2000;Crespo et al, 2003). In addition, ET-1 (a vasoconstrictor peptide secreted from endothelial cell) is thought to play a pathological role in a number of vascular diseases (Goto et al, 1996). Interestingly, it was recently reported that ET-1 can activate PI3-K in several cells (Ishibashi et al, 2000;Kawanabe et al, 2003) and that ET-1 activates NAD(P)H oxidase and induces superoxide production in cultured endothelial and smooth muscle cells (Duerrschmidt et al, 2000;Wedgwood et al, NAD(P)H oxidase is increased in STZ-induced diabetic aortae (Kanie and Kamata, 2002) and that this increase is normalized by the endothelin antagonist, J-104132, suggesting that ET-1 is involved in the increased formation of superoxide anions.…”
Section: Mechanisms Underlying Impaired Endothelial Function In Diabementioning
confidence: 99%
“…Endothelin-1 (ET-1), a vasoconstrictor peptide secreted from endothelial cells, is thought to play a pathological role in a number of vascular diseases (Goto et al, 1996). Plasma ET-1 levels are increased in the diabetic state (Takahashi et al, 1990;Makino & Kamata, 1998;Makino et al, 2001) and the plasma concentration of big endothelin-1, the precursor of ET-1, is elevated in patients with diabetes mellitus (Tsunoda et al, 1991).…”
Section: Introductionmentioning
confidence: 99%